Perbedaan Iklim Organisasi Sekolah pada SD Negeri dan Swasta - Chandra, Karen; Moerkardjono, Sukma Rani (Noetic Psychology, 2014)
AbstrakOrganizational climate will affect the organizational quality and achievement. In educational field, there were organizational school climate which occurs as a perception of school climate from the principal, teachers, students and school employee. This research aim to found out the difference in organizational climate between state primary school and private primary school in Central Jakarta.ÃÂ Using cluster ramdom sampling technique, two state primary school and two private primary school chosen as subject. School organizational climate measured with organizational climate indes from Hoy and Miskel (2001). The result showed there was no differences in organizational climate between private and state primary school. Kata kunci: organizational climate, primary schoolÃÂ